Rapid assembly of branched mannose oligosaccharides through consecutive regioselective glycosylation: A convergent and efficient strategy. Issue 27 (6th July 2017) - Meng, Bo; Wang, Jun; Wang, Qianli; Serianni, Anthony S.; Pan, Qingfeng
Abstract: A convergent and efficient strategy for the synthesis of high-mannose oligosaccharides is described wherein regioselective glycosylations between trichloroacetimidate donors and partially protected acceptors are employed to reduce the number of protection–deprotection steps. Two representative branched mannose oligosaccharides, a mannose heptasaccharide (Man7 ) and a mannose nonasaccharide (Man9 ) were constructed via (4 + 3) and (5 + 4) glycosylations, respectively. These mannose-containing oligosaccharides were obtained in nine steps in ∼25% overall yield and >98% purity on 60–70 mg scales to demonstrate the effectiveness of the strategy. Graphical abstract: